The Triumph of (Underlying)Ideology Over Populism in Western Europe - Fernández-García, Belén (Frontiers in Political Science, 2021)
The prototypical form of populism in Europe has been that of the radical right, which combines populism with nationalism, xenophobia and certain doses of authoritarianism. European left-wing populism, for its part, had remained a marginal phenomenon until the outbreak of the economic crisis in 2008. Since then, populism has ceased to be a phenomenon almost exclusively for the radical right and has spread along the ideological spectrum or has appeared with ambiguous ideological positions. The recent electoral advances of populism in Europe have led to the formation of coalition governments between populist parties of different ideological signs (first in Greece, then in Italy). Likewise, the programmatic evolution followed by some populist parties (e.g., the populist radical right's shift to the economic center, or even center-left) or some similarities between these parties beyond their populist rhetoric (e.g., Euroscepticism), indicates that European populist parties may have more in common than might be expected. This leads us to the following question: Are we witnessing the triumph of populism over ideology? That is, do left and right populist parties tend to converge on other issues that are beyond their populist rhetoric? Or do left-right differences remain hegemonic? This article aims to contribute to a better understanding of the nature of populism in Europe. In particular, this article aims to determine whether underlying ideology triumphs over populism in these types of political organizations or not. In order to do that, this study will analyze the ideological positioning and cohesiveness of populist parties in Western Europe at both party and electorate levels. Therefore, the ultimate goal of this research is to shed light on a phenomenon that is advancing electorally in Europe and that could determine future coalitions and government alliances.